The Rise of Interactive Governance and Quasi-Markets
X, 281 p.
Keywords: It has taken a long time to make this book. Many initial drafts of the chapters published in this book were presented in November 2000 during a two-day conference on Interactive governance: towards a post-parliamentary democracy held in Enschede (The Netherlands). The Netherlands Institute of Governance (NIG) sponsored the . conference. After this conference the organisers discussed the possibility of making a book on the basis of papers presented at this event. In the end it was agreed that such a publication would indeed be worthwhile provided the initial papers were fundamentally revised. Moreover it was agreed that also supplementary chapters should be included, in order to strengthen the international comparative perspective. On this basis authors of the conference papers chapters and envisioned new chapters were invited to (re)submit drafts. The completion of the book, however, was unexpectedly halted by the tragic sudden death of our co-editor and dear friend Oscar van Heffen. In his lifetime he was the driving force behind this project. Without his efforts, insightful comments and helpful suggestions this book, in its present form, would never have been published. As such we dedicate this volume to his memory, the completion of the book being an honorary debt to our friend and his wife Mirjan.